Simulation of a grid network with virtual machines to create a learning environment of high performance computing - Millán-Rojas, Edwin Eduardo; Gallego-Torres, Adriana Patricia; Chico-Vargas, Diana Carolina (Universidad Pedagógica y Tecnológica de Colombia, 2016)
This research presents a methodology for building a Grid platform to simulate a network with virtual machines in order to create virtual environments that contribute to the learning process. The design used for the development is based on a prototype that helps to generate a low cost simulation environment through the high-performance computing. As a result of the investigation a set of virtual machines that can be deployed on any computer equipment to simulate a Grid environment, was obtained. Besides the form of the configuration of this network is to be an integral part of the construction and design of the platform which is presented as valid instrument for the teaching of high performance computing at a low cost hardware, and simulation of Grid services on the instrument platform.